Post election, let the healing begin - EUGENE, Tan K. B. (Institutional Knowledge at Singapore Management University, 2011)
Assistant professor of law Eugene Tan notes in his commentary that a more complex global environment, a rapidly changing Singapore and the challenges it faces will require political parties and Singaporeans alike to mature politically so that Singapore's politics will not limit its potential as a nation.